Travels and adventures of an orchid hunter : an account of canoe and camp life in Colombia, while collecting orchids in the northern Andes / by Albert Millican ; illustrated by Gustave Guggenheim, from photographs by the author (1891)
This book aims at representing to the reader, and especially the lover of oorchids, the circumstance under which these plants are found in the north of South America, as well as being a guide to the traveller in Colombia and the West Indies ; besides endeavouring to set forth the natural riches of the country and the manners of the various classes of people, from the wild Indian of the forest to the polished and educated senator of the court. It is not a missionary’s report, nor a traveller’s diary, nor a student´s compilation, buy a narrative of things seen and experienced by me while travelling with natives through the forest, sharing with them the hospitality of the wayside hut or the forest shelter and the camp-fire, as well as the more agreeable life of hotels and towns. The information contained in this volumen has been gathered over a period of four years, during which I have made five journeys to the orchid districts of South America, the time occupied being generally from the month of october to the month of july. The greater parto f the illustrations are from photographs taken by me, more especially those of the plant pictures in the forest. Both plant-collectors and dealers have doubted the possibility of this, because they have not before been able successfully to photograph Odontoglossum Alexandre on its native trees, or the native means used to drag the plants from their cold, damp Andean home. But, as I still hold the original negatives, I shall be pleased to show them to any unbeliever